OUMH1303 English For Oral Communication :Tutorial 1 ; Part 4 - Adam Prakash Abdullah, (2010)
Topic 1 gives you an overview of communication in general, including what communication is all about, the types and purposes of communication, etc. You will be introduced to three models of communication - the linear, interactive and transactional models. This topic also covers different forms of communication including interpersonal, intrapersonal, small group, mass, public, corporate andcross-cultural communication.